Pendidikan Doktoral Kyai dan Modernisasi Pesantren: Implikasi Terhadap Pengembangan Ilmu dan Akhlak Santri - Maya Sari Pelangi (Universitas Islam Tribakti Lirboyo Kediri, 2026)
The increasing number of kyai (Islamic boarding school leaders) pursuing doctoral education reflects a significant transformation in the leadership of Indonesian Islamic boarding schools (pesantren). This study aims to examine the implications of doctoral education for the modernization of pesantren, particularly its impact on the development of students' knowledge and moral character. Employing a qualitative library research approach with descriptive-analytical methods, the study analyzes relevant literature on Islamic education, leadership, and educational modernization. The findings reveal that doctoral education strengthens the academic capacity of kyai by integrating the traditional epistemology of pesantren with modern academic scholarship. This integration contributes to the enhancement of research culture, curriculum innovation, scientific literacy, and national as well as international academic networks within pesantren. At the same time, doctoral-educated kyai play a crucial role in preserving the moral and spiritual values that characterize Islamic boarding school education through exemplary leadership and the integration of intellectual and ethical development. Nevertheless, this transformation also presents epistemological and cultural challenges, including tensions between traditional religious authority and critical academic approaches, as well as the risk of excessive academization. The study concludes that doctoral education serves as a strategic instrument for strengthening the adaptive capacity of pesantren while maintaining its Islamic identity, provided that kyai are able to balance tradition and innovation in responding to contemporary educational challenges.